1989
DOI: 10.1111/j.1600-0609.1989.tb01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myelogenous leukemia and Klinefelter's syndrome

Abstract: A case of chronic myelogenous leukemia with Klinefelter's syndrome mosaicism in a 27‐yr‐old male is reported. Cytogenetic analysis provided evidence that the Philadelphia chromosome occurred monoclonally in the XXY cells but not in the XY cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
1
Order By: Relevance
“…[491011] In all these cases the KS was incidentally detected during the routine cytogenetic evaluation for CML. Oguma et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[491011] In all these cases the KS was incidentally detected during the routine cytogenetic evaluation for CML. Oguma et al .…”
Section: Discussionmentioning
confidence: 99%
“…Oguma et al . [10] in their study have reported a 2-year old CML patient who had KS. The cytogenetic analysis showed that the Ph chromosome occurred monoclonally in the XXY cells but not in XY cells.…”
Section: Discussionmentioning
confidence: 99%
“…Un certain nombre de facteurs génétiques et environnementaux associés à un risque accru de développer des leucémies est incriminé. D'après Muts et al le phénotype myéloïde prédomine au cours du SK, comme dans le cas de notre patient, mais d'autres hémopathies malignes peuvent être observées [3,9], telles les leucémies aiguës lymphoblastiques [10], les syndromes lymphoprolifératifs [11] ou myéloprolifératifs [12]. L'association entre le SK et les leucémies aiguës a été décrite dans la littérature [7,8].…”
Section: Discussionunclassified